Discovery of N′-(1-(coumarin-3-yl)ethylidene)benzenesulfonohydrazide as a novel wound healing enhancer: synthesis, biological assessment, and molecular modeling - Eman F. Khaleel; Heba Abdelmegeed; Abdel-Razik H. Abdel-Razik; Manal S. Ebaid; Manal S. Ebaid; Ninh The Son; Nguyen Xuan Ha; Hoda Atef Abdelsattar Ibrahim; Mohamed A. Abdelrahman; Mohamed A. Abdelrahman; Abdelsamed I. Elshamy; Jarosław Dziadek; et al. (Frontiers in Chemistry)
Wound healing poses a considerable challenge in the domain of medical science. In modern clinical practice, there is a growing trend towards using herbal compounds to aid in the repair process. Among these, coumarin, a phytochemical recognized for its antibacterial and wound-healing properties, has attracted significant interest. Consequently, the current research explores the potential benefits of employing coumarin to enhance wound healing in a murine model. The compound N′-(1-(7-hydroxy-2-oxo-2H-chromen-3-yl)ethylidene)-4-methylbenzene sulfonohydrazide (CBSH) was synthesized through the condensation of 7-hydroxy-3-acetyl coumarin with p-toluenesulfonylhydrazide and subsequently assessed for its antibacterial efficacy. CBSH showcased impressive antimicrobial prowess, demonstrating the values of minimum inhibitory concentration (MIC) 50, 40, and 40 μg/mL against the notorious Staphylococcus aureus MRSA, the resilient Bacillus cereus, and the formidable Pseudomonas aeruginosa. Subsequent in vitro and in vivo experiments were performed to assess its impact on the healing of skin wounds. The results indicated that CBSH significantly promotes the migration of skin fibroblast cells and enhances the wound healing process. Additionally, it facilitated the complete re-epithelialization of wounds. The formation of well-structured granulation tissue, along with a decrease in indicators of wound infection, is supported by histological analysis that demonstrates a minimal presence of inflammatory cells compared to untreated wounds. Furthermore, in silico molecular docking studies targeting key proteins involved in skin wound healing (COX-2, 5-LOX, COX-1, and TNF-α) demonstrated that COX-2 exhibited the highest binding affinity for CBSH, along with a stable complex during molecular dynamics simulations. Collectively, the results of this study indicate that CBSH may have a protective effect against infections in skin wounds, attributable to its antimicrobial properties.